Teacher-mediated intervention after disaster: a controlled three-year follow-up of children's functioning - (:unkn) unknown (WILEY, 2005)
Background: Child survivors of a catastrophic earthquake in Turkey were evaluated three and a half years after the event, and three years after a sub-group participated in a teacher-mediated intervention developed by the authors. The goal of this follow-up study was to determine the long-term effectiveness of the original intervention. Methods: Subjects who participated in the intervention were compared with a control group of children similar in terms of demographics, risk and exposure. All children were evaluated in terms of posttraumatic, grief and dissociative symptomatology, as well as adaptive functioning (academic performance, social behavior and general conduct). Results: The severity of post-traumatic, grief and dissociative symptoms of the two groups was comparable. Teachers blind to group assignment rated participating children significantly higher than the control group in terms of adaptive functioning. Conclusions: Early post-disaster intervention addressing children and their educational milieu provides children with significant symptomatic reduction, allowing the mobilization of adaptive coping, thereby enhancing their overall functioning as observed in school.
Keywords: children; trauma; disaster; school intervention; adaptation; POSTTRAUMATIC-STRESS; NATURAL DISASTER; TRAUMA; SYMPTOMS; SCHOOL; ADOLESCENTS; SURVIVORS; WAR; PSYCHOTHERAPY; TERRORISM